UPLC-MS metabolite profiling and antioxidant activity of Sanghuangporus sanghuang extract - Weike Wang; Na Lu; Cheng Jiang; Guanping Chen (PeerJ)
Background The objective of the present study is to examine the total phenolic and flavonoid content of an ethanol extract of Sanghuangporus sanghuang and to evaluate its phytochemical properties, antioxidant activity, and capacity to protect DNA from damage. This pharmaceutical/food resource mushroom may serve as a novel substitute functional food for health-conscious consumers, given its promising source of phenolics and flavonoids. Methods S. sanghuang ethanol extract (SEE) was evaluated for total phenolic and flavonoid contents, while UPLC-MS analysis was used for terpenoids, phenylpropanoid, flavonoids, steroidal, phenols identification, and function prediction. Antioxidant and anti-DNA damage activities were tested in vitro using ferric reducing antioxidant power (FRAP), 1,1-diphenyl-2-picrylhydrazyl (DPPH), 2,2′-azino-bis-3-ethylbenzotiazolin-6-sulfonic acid (ABTS), and DNA damage protection assay. Results and Conclusion Total phenolic content (TPC) in SEE was 385.38 ± 1.36 mg GA/g extract, while total flavonoid content (TFC) was 298.22 ± 2.38 mg QE/g extract. The extracts exhibited high antioxidant and free radical scavenging activities with relatively stronger free radical scavenging activity. A total of 491 metabolites were investigated by Ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). Most of the top 20 compounds were predicted to have various functions like antioxidant, anti-cancer and anti-inflammatory. This study highlighted S. sanghuang was a beneficial source of phenolics and flavonoids. It contains potential natural antioxidant that could be used as a lead contender in the development of antioxidant medicines for the treatment of a wide range of oxidative stress-related illnesses.